Toefl Preparation Program at SMA Negeri 3 Sidoarjo to Improve Academic Reading Ability: A Student Based - Imroatul Asheila Almasih; Rakhmawati; Nafidatul Hikmah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study examined the implementation of the TOEFL preparation program at SMA Negeri 3 Sidoarjo and its impact on students' reading skills. The study used a qualitative approach and collected data using open-ended questionnaires completed by participating students. The data were then analyzed by thematic grouping to determine learning experiences, reading strategies used, and barriers encountered during the learning process. The results showed that the program had a positive impact on reading skills, particularly on vocabulary mastery through speed-reading strategies such as skimming and scanning, and increased confidence in dealing with academic texts. Students also demonstrated independent learning by practicing independently, using digital applications, and memorizing new vocabulary. However, several barriers were identified, such as a lack of vocabulary mastery, difficulty understanding complex sentences, and overly repetitive teaching methods. Based on the research findings, the TOEFL preparation program needs to be improved through more interactive methods, more diverse learning strategies, and school support. Furthermore, students should be grouped according to their language level to increase learning effectiveness. This study concludes that the TOEFL preparation program can significantly improve students' academic reading skills, although improvements in learning design and support from educational institutions are still needed.